Luctuoso setiembre: el informe del Dr. Alexander von Frantzius sobre los sucesos de 1860 en Puntarenas - Hilje-Quirós, Luko (2012)
A hero of the National Campaign against the filibuster army led by William Walker, Juan Rafael Mora, president of Costa Rica, was overthrown and deported to El Salvador in 1859. A year later he returned to attempt to regain power, but after military confrontations in Puntarenas, he failed and was shot, along with his collaborators Ignacio Arancibia and José María Cañas. In his role of the Army`s Chief Surgeon, the German Alexander von Frantzius prepared a detailed report to the government about those bloody days. So far unpublished, because of its great historical value, the original report is herewith published, complemented with some explanatory footnotes.